2012
DOI: 10.1021/ie202305m
|View full text |Cite
|
Sign up to set email alerts
|

Ideal CO2/Light Gas Separation Performance of Poly(vinylimidazolium) Membranes and Poly(vinylimidazolium)-Ionic Liquid Composite Films

Abstract: Six vinyl-based, imidazolium room-temperature ionic liquid (RTIL) monomers were synthesized and photopolymerized to form dense poly(RTIL) membranes. The effect of polymer backbone (i.e., poly(ethylene), poly(styrene), and poly(acrylate)) and functional cationic substituent (e.g., alkyl, fluoroalkyl, oligo(ethylene glycol), and disiloxane) on ideal CO2/N2 and CO2/CH4 membrane separation performance was investigated. The vinyl-based poly(RTIL)s were found to be generally less CO2-selective compared to analogous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
109
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(115 citation statements)
references
References 52 publications
6
109
0
Order By: Relevance
“…Indeed, to our knowledge the permeability of 186 barrers measured for the poly([P 888VB ][Tf 2 N]) membrane is the highest reported for a neat PIL membrane, surpassing even siloxane-functionalized imidazolium PILs(Figure 4) (max. 130 barrers) while maintaining comparable CO 2 /N 2 selectivity (15 vs. 14) 22. The higher CO 2 permeability of poly([P 888VB ][Tf 2 N]) can be explained by comparing the gas diffusivities for CO 2 and CH 4 in each material (…”
mentioning
confidence: 99%
“…Indeed, to our knowledge the permeability of 186 barrers measured for the poly([P 888VB ][Tf 2 N]) membrane is the highest reported for a neat PIL membrane, surpassing even siloxane-functionalized imidazolium PILs(Figure 4) (max. 130 barrers) while maintaining comparable CO 2 /N 2 selectivity (15 vs. 14) 22. The higher CO 2 permeability of poly([P 888VB ][Tf 2 N]) can be explained by comparing the gas diffusivities for CO 2 and CH 4 in each material (…”
mentioning
confidence: 99%
“…In contrast, Bara et al 24 exhibited the greatest gas permeabilities, but presented the lowest selectivities. 24 Later, Carlisle et al 25 The disiloxane-functionalized vinylimidazolium PIL showed the highest CO 2 permeability but low CO 2 /N 2 and CO 2 /CH 4 selectivities. 25 Furthermore, polydimethylsiloxane (PDMS) has been commonly used for several gas separation applications not only due its chemical and thermal stabilities and low price, but also because of its high permeability to a wide range of gas species, justified by its chain flexibility and large free volume.…”
Section: Introductionmentioning
confidence: 99%
“…24 Later, Carlisle et al 25 The disiloxane-functionalized vinylimidazolium PIL showed the highest CO 2 permeability but low CO 2 /N 2 and CO 2 /CH 4 selectivities. 25 Furthermore, polydimethylsiloxane (PDMS) has been commonly used for several gas separation applications not only due its chemical and thermal stabilities and low price, but also because of its high permeability to a wide range of gas species, justified by its chain flexibility and large free volume. [26][27][28][29] In the present work, the gas permeation properties and CO 2 The highest relative standard uncertainty registered for the dynamic viscosity and density measurements was 0.03 and 2·10 −4 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of diversity in what concerns the different chemical structures of cations and anions is another key issue, since the majority of the efforts to use PIL-IL membranes for CO 2 separation used imidazolium moieties as pendant groups of the polycation backbone and the bis(trifluoromethylsulfonyl)imide ([NTf 2 ] À ) as counter-anion [57][58][59][60][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%